남자 고등학교 스포츠 클라이밍 우수 선수와 비우수 선수의 체력 및 등반 중의 심박수와 혈중 젖산농도의 비교 - 손정준; Jung Jun Son; 이만균; Man Gyoon Lee; 홍광석; Kwang Seok Hong (Ch'eyuk kwahak yŏn'gu, 2008)
최근 스포츠 클라이밍이 생활체육으로서 널리 보급되고 있고, 스포츠 클라이밍 선수의 수도 급증하고 있다. 그러나 이 종목에 대한 운동과 학적 연구가 상당히 미흡한 실정이다. 본 연구의 목적은 남자 고등학교 스포츠 클라이밍 우수 선수와 비우수 선수의 체력 및 등반 중의 심박수와 혈중 젖산농도를 비교하는 것이었다. 본 연구의 대상은 남자 고등학교 스포츠 클라이밍 선수 18명으로서, 이들을 우수 선수 집단 9명과 비우수 선수 집단 9명으로 구분하였다. 모든 피검자를 대상으로 신체구성 검사와 체력 검사를 실시하였고, 실외 인공암벽등반 코스에서 난이도가 다른 두 가지 형태의 루트(요세미티 등급체계의 5.10b급과 5.12b급)를 등반하도록 하였다. 이와 같이 난이도가 다른 두 가지 루트를 등반하도록 한 후 등반 중과 회복기 동안 심박수와 혈중 젖산농도를 측정하였다. 본 연구에서 얻은 결과를 요약하여 기술하면 다음과 같다. 우수 선수 집단은 체지방량과 체지방률이 비우수 선수 집단에 비하여 유의하게 낮게 나타났다. 팔굽혀펴기와 턱걸이는 우수 선수 집단이 비우수 선수 집단에 비하여 높은 것으로 나타났다. 그러나 최대산소섭취량의 경우 두 집단 간에 유의한 차이가 나타나지 않았다. 루트 1 등반 중과 회복기의 심박수는 우수 선수 집단이 비우수 선수 집단에 비해 유의하게 낮았으며, 루트 1 등반 후 회복기 10분에서의 혈중 젖산농도는 우수 선수 집단이 비우수 선수 집단보다 유의하게 낮게 나타났다. 루트 2 등반 중의 심박수에서는 두 집단 간에 유의한 차이가 나타나지 않았다. 본 연구에서 얻은 결과를 통해, 남자 고등학교 스포츠 클라이밍 선수는 경기력 수준이 높을수록 체지방률이 낮고, 상완 근지구력이 우수하며, 낮은 난이도의 루트 등반 중 순환계 기능이 우수하고 혈중 젖산에 대한 내성과 제거 능력이 우수한 것으로 결론지을 수 있다. The study was designed to compare body composition, physical fitness, heart rate and blood lactate concentration during sports climbing between superior athletes and inferior athletes in male high school sports climbing. Nine superior athletes and nine inferior athletes participated in body composition and physical fitness tests, and then they were asked to climb two level of outdoor artificial rock climbing routes(5.10b and 5.12b in the Yosemite Decimal System). While all subjects were climbing the two different level of routs, heart rate and blood lactate level were measured. Results of this study were as follows: The superior athletes had lower percent body fat and body fat mass than the inferior athletes, and the superior athletes did more push-ups and chin-ups for testing muscular endurance than the inferior athletes. There was not a significant difference in maximal oxygen uptake between the two groups. The superior athletes had lower heart rates during and after the route 1 than the inferior athletes. The superior athletes also showed a lower blood lactate concentration for 10 minutes of recovery phase after the route 1. It was concluded that the superior sports climbing athletes have better and more positive body composition, physical fitness(especially arm muscular endurance), and that they showed a better metabolism and recovery than inferior athletes while doing an easy route. Therefore, we should find new ones who have a native talent to be an outstanding sports climbing athlete, and sports climbing athletes have to develop arm muscular endurance, physical fitness, and skills to improve athletic performance. To do that, more sports climbing athletes have to practice climbing in a situation similar to real mountain climbing and do more research for ordinary people as well as athletes to show the effect of sports climbing.